PENGARUH MEDIA PEMBELAJARAN BERBASIS ONLINE TERHADAP MOTIVASI BELAJAR EKONOMI PESERTA DIDIK PADA MASA PANDEMI COVID-19 DI SMA NEGERI 11 PONTIANAK - Sari, Mega Wulan; Syahrudin, Husni; Syamsuri, Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The student learning process can be successful if there is a willingness to learn within students, including in online-based learning media. The learning media used when carrying out online learning at SMA Negeri 11 Pontianak are the Whatsapp, Classroom, and Google Meet applications. The purpose of this study was to determine the effect of online-based learning media on the economics learning motivation of class XI IPS students during the Covid-19 pandemic at SMA Negeri 11 Pontianak. In this study, researchers used a quantitative approach to the survey method. The technique used is indirect communication. Data collection tool used is a questionnaire (questionnaire). The results showed that there was a positive and significant influence of online-based learning media on students' motivation to study economics. This can be seen from the results of simple linear regression, namely through the t test, the magnitude is 0.05. The tcount value is 3.017 and the significance is 0.004. While the results obtained for the table is 1.944. Thus it is known that the value of tcount ttable (3.017 1.944), and significance 0.05 (0.004 0.05), then Ha is accepted. From the study, it was obtained that the regression coefficient (R2) of the X variable was 0.394 which stated that there was a media effect between online-based learning media on the variable economic learning motivation of class XI IPS students at SMA Negeri 11. Pontianak by 11.5%